The Role Of Correctional Officers In Combating The Entry Of Prohibited Goods In Class II Langkat Prison - Mitranda Seragih; Yasmirah Mandasari Saragih (International Journal of Law and Society, 2024)
The circulation and misuse of prohibited narcotics in society must be prevented and addressed. These prevention efforts must be strictly implemented in accordance with Law Number 35 of 2009 concerning Narcotics so that the problem of prohibited narcotics does not continue to grow in society as an epidemic that is bad for the development of the country. A number of cases of distribution of prohibited narcotics in prisons continue to be uncovered. Both in correctional institutions in big cities and in other small cities. The method is the same, carried out via cellphone and internet communication. In fact, it is absolutely impossible for a prison inmate to be able to freely use a cellphone and internet connection in a correctional institution. Because communication tools are prohibited items for a prison inmate. Correctional officers also admitted that they often carry out inspections of detention rooms, searching the prison inmates' possessions. The nature of the research used by the author in this law journal is analytical descriptive because this research describes in detail the social phenomena that are the subject of the problem. A descriptive study is intended to provide as precise data as possible about people, conditions or other symptoms. The type of research used in this writing is empirical juridical research, namely research into problems by looking at and paying attention to applicable legal norms connected to existing facts from the problems encountered in the research. Library Research (Library Research). The factors causing the increasing level of narcotics abuse consist of internal and external factors. The internal factors are religious factors and family factors, while external factors consist of economic and educational factors as well as social factors / environmental influences. The Langkat Class II Youth Correctional Institution has carried out both preventive and repressive measures against perpetrators of crimes involving prohibited narcotics, including providing counseling, coaching and arresting both the public and perpetrators of narcotics crimes. The application of legal sanctions against perpetrators continues to refer to the provisions regulated in Law Number 35 of 2009. In general, perpetrators of crimes involving prohibited narcotics in class II youth correctional institutions are users/using prohibited narcotics for their own consumption (addicts) so that sanctions are alleged to be violations of the provisions for users/consumers of prohibited narcotics.